Preventive Strategies for Atrial Fibrillation After Cardiac Surgery in Nordic Countries. (September 2013) - Maaroos, M.; Tuomainen, R.; Price, J.; Rubens, F. D.; Jideus, R. L.; Halonen, J.; Hartikainen, J.; Hakala, T.
Background and Aims: Atrial fibrillation is a common arrhythmia after cardiac surgery. It increases morbidity, length of hospital stay, and costs of operative treatment. Beta-blockers, sotalol, amiodarone, corticosteroids, and biatrial pacing have been shown to be efficient in the prevention of postoperative atrial fibrillation. The aim of this study was to find out how widely different prophylactic strategies for postoperative atrial fibrillation are used in Scandinavian countries. Material and Methods: An online link for a questionnaire was emailed to (214) cardiac surgeons in Finland, Sweden, Norway, Denmark, and Estonia to assess the use of prophylactic methods for postoperative atrial fibrillation. Results: A total of 97 surgeons responded to the survey. Oral beta-blockers were routinely used for atrial fibrillation prophylaxis by 62% of responders. The main reasons for nonuse of beta-blockers were that responders were unconvinced of the evidence of benefit or they preferred some alternative prophylaxis. Intravenous beta-blockers were used frequently by 6% of responders. Amiodarone was used for prophylaxis by 18% of responders. Nonusers were unconvinced of its efficacy, were afraid of its complications, or found its use too cumbersome. Other prophylactic atrial fibrillation strategies that were used are as follows: sotalol by 2%, magnesium by 17%, corticosteroids by 1%, and atrial pacing by 11% of respondents. Conclusions: There is still widely varying implementation of strategies for atrial fibrillation prophylaxis among Scandinavian cardiac surgeons. Lack of confidence in the efficacy of these approaches is the main rationale for nonimplementation.